A two-phase simulation for analyzing the hydraulic-thermal performance of Cu–Water nanofluid within a tube enhanced with W- and C-shaped ribs. (March 2023) - Zhou, Yuan; Bu sinnah, Zainab Ali; Yasin, Yaser; Salman, Nawras Ali; Jaber, Asala Salam; Abdulkadhim, Adnan Hashim; AL-Khafaji, Mohsin O.; Nasajpour-Esfahani, Navid; Marashi, Mahzyar; Golzar, Ali; Toghraie, Davood
Abstract: The present study numerically investigated the simulation of two-phase nanofluid (NF) flow to examine the thermal performance of Cu–water NF within an enhanced tube with W- and C-shaped ribs in the heat exchangers (HEX). In this research, the effect of volume fraction (φ = 0.2, 0.4, 0.6, and 0.8%), and diameter (15, 20, 25 and 30 nm) of copper nanoparticles and the type and size of the turbulators (TRB) (W- and C-shaped ribs together), which were designed for the first time on Heat transfer (HT), were discussed. Heat transfer flow (HTF) entered the test section at T in  = 290 K in various velocities related to different Reynolds numbers (Re) 5000, 10000, 15000 and 20000. Based on the Eulerian-Eulerian two-phase method, the governing equations were solved. Different rib geometrical parameters were determined, and the optimization was performed to achieve the maximum performance evaluation criteria (PEC). According to obtained results, the PECs were more than 1, which indicated that these TRB were impressive from a hydraulic-thermal performance. Furthermore, the PEC variations of C- and W-shaped models were not similar. For the C-shaped configuration, the PEC values always enhanced with Re enhancement, while for the W-shaped model, the PEC values enhanced till Re = 10000, and then decreased till Re = 20000. The PEC values of the optimum model (W-shaped, NB  = 6 and R  = 15 mm) filled by NF at φ  = 0.8% and d np  = 30 nm in Re = 5000, 10000, 15000 and 20000 are 1.491, 1.498, 1.482 and 1.469, respectively.